2018
DOI: 10.1186/s40985-018-0102-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing trauma in a transcultural context: challenges in mental health care with immigrants and refugees

Abstract: The growing numbers of refugees and immigrants from conflict-prone areas settling throughout the world bring several challenges for those working in the mental health care system. Immigrants and refugees of all ages arrive with complex and nuanced mental health histories of war, torture, and strenuous migration journeys. Many of the challenges of addressing the health care needs for this growing population of immigrants and refugees are often unfamiliar, and thus practices to address these challenges are not y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 40 publications
3
55
0
2
Order By: Relevance
“…Most GPs in our study stated that they felt their education had not adequately prepared them for working with refugees suffering from mental health problems. Other studies found that clinicians lack a uniform procedure to deal with such consultations (Wylie et al, 2018), lacked support or resources (Begg and Gill, 2005), and sufficient education and supervision (Fuller, 1993). While participants in our study pointed out that their education may not have prepared them for this work theoretically, they believed that their practical experience had.…”
Section: Summary Of Themesmentioning
confidence: 63%
See 4 more Smart Citations
“…Most GPs in our study stated that they felt their education had not adequately prepared them for working with refugees suffering from mental health problems. Other studies found that clinicians lack a uniform procedure to deal with such consultations (Wylie et al, 2018), lacked support or resources (Begg and Gill, 2005), and sufficient education and supervision (Fuller, 1993). While participants in our study pointed out that their education may not have prepared them for this work theoretically, they believed that their practical experience had.…”
Section: Summary Of Themesmentioning
confidence: 63%
“…Language barriers posed an important challenge both in our study and in previous literature (Jensen et al, 2013;Wylie et al, 2018). The 'circling the undefined' model highlights that information needs to be shared in order for clinician and patient to clarify those issues that are fundamental to the consultation, such as what constitutes health and illness (Rothlind et al, 2018).…”
Section: Summary Of Themesmentioning
confidence: 82%
See 3 more Smart Citations